2022
DOI: 10.1002/ijgo.14567
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for bladder injury during placenta accreta spectrum surgery

Abstract: Objectives To identify risk factors associated with bladder injury during placenta accreta spectrum (PAS) surgeries. Methods This retrospective cohort study was conducted at the Chaim Sheba Medical Center. The study population included pregnant women diagnosed with PAS undergoing uterine‐preserving surgery or hysterectomy. Women with and without operative bladder injury were compared by univariate analysis followed by multivariate analysis. A sub‐analysis of women without preoperative sonographic suspicion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The multidisciplinary team at Dr. Moewardi Hospital was successful in preventing urinary bladder and ureter injury, with only 9 bladder and ureter injury cases (5.4%), which is lower than the previous study by Mohammed et al (2018) with 31%, [49] Mitric et al (2019) with 12.7%, [26] and Friedrich et al (2022) with 9.3% [50] . The maternal ICU referral in Dr. Moewardi Hospital was also comparatively low, with only 11 out of 167 (6.6%) admissions, compared to previous studies by Mohammed et al (2018) with 42% admissions, [49] Kandil et al (2019) with 22.5% admissions, [18] and Ornaghi et al (2021) with 24% admissions [51] .…”
Section: Discussionmentioning
confidence: 58%
“…The multidisciplinary team at Dr. Moewardi Hospital was successful in preventing urinary bladder and ureter injury, with only 9 bladder and ureter injury cases (5.4%), which is lower than the previous study by Mohammed et al (2018) with 31%, [49] Mitric et al (2019) with 12.7%, [26] and Friedrich et al (2022) with 9.3% [50] . The maternal ICU referral in Dr. Moewardi Hospital was also comparatively low, with only 11 out of 167 (6.6%) admissions, compared to previous studies by Mohammed et al (2018) with 42% admissions, [49] Kandil et al (2019) with 22.5% admissions, [18] and Ornaghi et al (2021) with 24% admissions [51] .…”
Section: Discussionmentioning
confidence: 58%
“…A single‐center cohort study of 292 patients in the USA reported an incidence of 19.9% urologic morbidity, with a higher incidence in those patients diagnosed with placenta percreta 29 . Similarly, a single‐center cohort study of 312 patients in Germany found a bladder‐injury incidence of 9.3% with a higher risk in patients with ultrasound imaging suggesting a placenta percreta 30 . In view of recent evidence, indicating that normal villous tissue does not cross the uterine serosa 3,31 , these cases are likely to be the consequence of surgical dissection of a dehiscent LUS covered only by a thin layer of scar myometrium and single‐cell layer of serosa epithelium 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The contact between the injured uterus and bladder, results in their adherence during healing process 28 . This abnormal adherence is associated with an increased risk of bladder injury even outside the context of PAS which usually occurs during peritoneal entry or while creating the bladder ap [29][30][31] . This nding was also observed in a large retrospective cohort of PAS cases in Italy 32 .…”
Section: Discussionmentioning
confidence: 99%